PENERAPAN MEDIA PEMBELAJARAN VIDEO TUTORIAL TEKNIK MEMBATIK TERHADAP HASIL BELAJAR ELEMEN EKSPERIMEN TEKSTIL DAN DESAIN HIASAN SISWA KELAS XI TATA BUSANA SMKN 3 JEMBER - Kusumawati, Lestari; Marniati, Marniati (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2024)
This research aims to (1) investigate the implementation of instructional video tutorials on batik techniques in textile experimentation and decorative design and (2) examine students' responses to the elements of textile experimentation and decorative design by utilizing instructional video tutorials on batik techniques. A total of 27 students from class XI in the Fashion Design Department at SMKN 3 Jember were subjects in this study. The data utilized in this research were derived from observations and assessments of students' learning outcomes. The findings of this study reveal that (1) instructional video tutorials on batik techniques in the elements of textile experimentation and decorative design in class XI at SMKN 3 Jember are proven to be suitable for educational purposes and (2) students' responses to the elements of textile experimentation and decorative design using instructional video tutorials are highly positive and effectively motivate students to actively participate, maintain discipline, and take responsibility for learning batik techniques. This research also indicates that this media is effective in providing conceptual understanding and has a positive impact on students' practical skills mastery in batik